Duodenal Helminth Infection Alters Barrier Function of the Colonic Epithelium via Adaptive Immune Activation - Su, Chien-wen (American Society for Microbiology, 2011)

(untitled)
Chronic infection with intestinal helminth parasites is a major public health problem, particularly in the developing world, and can have significant effects on host physiology and the immune response to other enteric infections and antigens. The mechanisms underlying these effects are not well understood. In the current study, we investigated the impact of infection with the murine nematode parasite Heligmosomoides polygyrus, which resides in the duodenum, on epithelial barrier function in the colon. We found that H. polygyrus infection produced a significant increase in colonic epithelial permeability, as evidenced by detection of elevated serum levels of the tracer horseradish peroxidase following rectal administration. This loss of normal barrier function was associated with clear ultrastructural changes in the tight junctions of colonic epithelial cells and an alteration in the expression and distribution of the junctional protein E-cadherin. These parasite-induced abnormalities were not observed in SCID mice but did occur in SCID mice that were adoptively transferred with wild-type T cells, indicating a requirement for adaptive immunity. Furthermore, the helminth-induced increase in gut permeability was not seen in STAT6 knockout (KO) mice. Taken together, the results demonstrate that one of the mechanisms by which helminths exert their effects involves the lymphocyte- and STAT6-dependent breakdown of the intestinal epithelial barrier. This increase in epithelial permeability may facilitate the movement of lumenal contents across the mucosa, thus helping to explain how helminth infection can alter the immune response to enteric antigens.